Apolipoprotein E gene polymorphisms in relation to chronic periodontitis, periodontopathic bacteria, and lipid levels - Borilova Linhartova, Petra; Bartova, Jirina; Poskerova, Hana; Machal, Jan; Vokurka, Jan; Fassmann, Antonin; Izakovicova Holla, Lydie (Archives of oral biology, 2015)
OBJECTIVE: Inflammatory periodontal diseases may be associated with common systemic conditions and, as recently described, alterations in lipid levels in the blood. The aim of this study was to determine the possible effects of apolipoprotein E (ApoE) genotypes on the lipid levels in healthy people and patients with chronic periodontitis (CP) in relation to periodontopathic bacteria. DESIGN: This case-control study comprised 469 unrelated subjects. The genomic DNA of 294 patients with CP and 175 healthy/non-periodontitis controls were genotyped, using the real-time polymerase chain reaction (RT-PCR) method, for ApoE (rs429358 and rs7412) gene polymorphisms. Subgingival bacterial colonization was investigated by the DNA microarray using a periodontal pathogen detection kit and lipid levels were measured in a subgroup of subjects (N = 275). RESULTS: There was no evidence for a significant association between ApoE gene polymorphisms and CP (P > 0.05). Patients with CP had increased levels of total cholesterol and low-density lipoprotein (LDL) compared to controls (P< 0.05); however, no significant difference was found for triglyceride and high-density lipoprotein (HDL) levels. ApoE gene variability influenced LDL levels marginally (P = 0.08) but it did not modify total cholesterol, triglyceride, and HDL levels or the occurrence of periodontal pathogens in subgingival pockets.(23) CONCLUSIONS: In the Czech population studied, ApoE genetic variations were not associated with susceptibility to CP or the presence of periodontopathic bacteria.
Keywords: Male; mikročipová analýza; Middle Aged; kvantitativní polymerázová řetězová reakce; Genotype; Adult; Bacteria; Case-Control Studies; dospělí; mužské pohlaví; jednonukleotidový polymorfismus; Real-Time Polymerase Chain Reaction; chronická parodontitida; lipidy; Periodontitis; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; studie případů a kontrol; apolipoproteiny E; Humans; SNP; Microarray Analysis; genotyp; Lipids; Alleles; Female; alely; lidé středního věku; Chronic Periodontitis; ApoE gene; Apolipoproteins E